Meningkatkan Kemandirian Belajar Materi Pribadi Dengan Metode PBL Berbantuan Media Audio Visual Fase E Kelas X Sma Negeri 1 Nanga Taman Kabupaten Sekadau - Alponso Anselmus; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The independence and learning outcomes of students in Aku Pribadi yangUnik material Class X A of SMA Negeri 1 Nanga Taman are still low, partly because the teacher uses inappropriate methods. This study aims to improve student learning outcomes by applying the Problem Based Learning method assisted by audio-visual media on students' personal material.This type of research is Classroom Action Research (CAR) by providing action in two learning cycles, each cycle consisting of two meetings. This research was conducted in July and August 2023. The research subjects were 22 class X A students at SMA Negeri 1 Nanga Taman. Improved cognitive learning outcomes were obtained from the posttest theme 2 cycle 2, while the learning outcomes of Pancasila student profiles were obtained from observation and observation sheets.The results of the study show that the application of the Problem Based Learning model assisted by Audio-visual media can improve the cognitive and affective learning outcomes of Pancasila student profiles. In the cognitive aspect in cycle 1 there was still 40.91% of the acquisition of students' knowledge scores which were still below the KKTP, increasing to 0% in cycle 2. The increase also occurred in mahir and cakap predicates where in cycle 1 mahir was only 18% and cakap was 40% in cycle 2 increased to 54.55% mahir and 45.54% cakap. The conclusion of this study is that the application of the Problem Based Learning Model assisted by audio-visual media can improve the affective and cognitive learning outcomes of class X SMA Negeri 1 Nanga Taman on the Material Aku Pribadi yangUnik